Kinetics of the cercaria-schistosomul um transformation in vivo: 2. The effect of oxamniquine - A. L. Melo; L.H. Pereira (Sociedade Brasileira de Medicina Tropical (SBMT), 1985)
To study the cercaria-schistosomulum transformation in vivo, underthe influence of an antischistosomal compound (oxamniquine), a model using cercarial infections into the abdominal cavity of mice was chosen. This procedure provided easy and reproducible recoveries of larvae from peritoneal washings with appropriate solutions for a long time (30 to 180 min) after inoculation. The results show that high doses of oxamniquine (given intramuscularly one hour before the infection) produce a marked delay in the kinetics of the cercaria-schistosomulum transformation. Cercariae, tail-less cercarial bodies and schistosomula were recovered from the peritoneal cavity ofdrug treated mice in numbers significantly different from those recovered from untreated mice. Para estudar a transformação da cercária em esquistossômulo in vivo, sob a influência de um composto ativo contra o Schistosoma mansoni, foi escolhida a técnica da inoculação de cercárias na cavidade peritoneal de camundongos. Este procedimento se mostrou reproduzivel epromoveu uma rápida efácil recuperação das larvas após a lavagem das vísceras abdominais com solução apropriada. Os resultados obtidos sugerem que altas doses de oxamniquine (via intramuscular), uma hora antes da infecção, produzem um evidente atraso na cinética do processo de transformação da cercária em es-quistossômulo. Cercárias, corpos cercarianos e esquistossômulos foram recuperados da cavidade peritoneal de camundongos tratados em números diferentes daqueles recuperados dos animais controles.